Bio-succinic acid production from coffee husk treated with thermochemical and fungal hydrolysis - Dessie, Wubliker; Zhu, Junru; Xin, Fengxue; Zhang, Wenming; Jiang, Youming; Wu, Hao; Ma, Jiangfeng; Jiang, Min (Bioprocess and biosystems engineering, 2018)
Coffee husk (CH), a waste obtained from processing of coffee cherries via dry method, causes serious environmental problems. In this study, strategies were designed to utilize CH for succinic acid (SA) production. Three different CH hydrolysis methods: thermal, thermochemical and crude enzymes obtained by solid state fermentation of Aspergillus niger and Trichoderma reesei , were evaluated to generate fermentable feedstock for SA production using Actinobacillus succinogenes . The feasibility of these pretreatment methods was investigated. Accordingly, thermochemical hydrolysis using H 2 SO 4 at 121 °C for 30 min, appeared the most effective method for CH hydrolysis, producing 24.4 g/L of reducing sugars (RS). Finally, 19.3 g/L of SA with yield and productivity of 0.95 g SA/g RS and 0.54 g/L/h, respectively, were obtained using CH hydrolysate. The current study revealed an alternative way of utilization coffee waste for value addition while mitigating environmental problems caused by its disposal.